The Effect Of Breadfruit Flour Substitution On The Quality Of Bengkulu Bay Tat Cake - Reda Kurnia; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
Bay tat cake is a cake which means two syllables bay comes from the Bengkulu language which means parent, while tat means tart. This cake has a meaning as a typical Bengkulu tart. The main ingredient in making bay tat cake is wheat flour which is still imported. Imports of wheat flour can be reduced by developing products from local flour, such as breadfruit flour. Breadfruit flour is gluten-free flour produced from breadfruit and cultivated naturally, and contains high calcium and fiber so it can replace wheat flour”. This study discusses the effect of substitution of quality (shape, color, aroma, texture and taste) of bay tat cake with breadfruit flour as much as 25%, 50% and 75%. This type of research is purely experimental with a completely randomized design method (CRD) with three treatments and three treatments. The data used is primary data obtained directly from 3 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of breadfruit flour bay tat cake. The data that has been obtained is then tabulated in the form of a table and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount > Ftable, then it is continued with Duncan's test. The results showed that there was no significant effect on the quality of the shape, color, texture and taste of breadfruit flour bay tat cake. but there is a significant effect on the quality of the aroma of the bread tat bay tat cake. The results of the quality test of the best bay tat breadfruit flour cake are on the quality of the neat square shape X0, the quality of the surface shape X2, the quality of the yellow-brown color X1, the quality of the fragrant aroma X0, the quality of the solid texture X2 and the quality of the taste X0.